Da’wah through the Webtoon Series Ngopi Yuk - Muhammad Taufiqur Rohman; Abdullah Sattar (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2023)
Webtoon is a digitization of conventional comic books, which is supported by internet technology so that the reach of readers becomes wider. This study examines the da'wah messages in the Webtoon series Ngopi Yuk! episode 860. The research used textual analysis and Roland Barthes' semiotics approach. The research results have found two aqidah teachings about death and believing in the destiny of Allah SWT. Another message found in this research is about a moral teaching that is, avoiding arrogant attitudes. No sharia preaching messages were found in this study.